Direito e Neoliberalismo Tecnologias Jurídicas e Governamentalidade em Michel Foucault - Silva, Thiago Mota Fontenele e (2018)
How law and neoliberalism relate in the history of governmentality developed by Michel Foucault? To answer this question, we take as main sources the two courses that he delivered in the late 1970s: Security, Territory, Population and The Birth of Biopolitics. The exposé has five chapters. In the first, Method Issues in Genealogical Analysis, we present some important general notions in Foucault’s thought (genealogy, biopower, governmentality, etc.), in order to guarantee the rigor of its use in the historical analyzes of the following chapters. In the second chapter, Reason of State, Political Technologies and Law, we go back to the end of the 16th century, aiming to investigate the reason of State as a remote point of provenance in the genealogy of neoliberalism. Supported by mercantilism, the reason of State targets the State itself and mobilizes two technological ensembles, the diplomatic-military apparatus and the police State. In this context, the law externally limits the governmental practices. In the third chapter, Political Economy, Law and Liberalism, we advanced towards the end of the 18th century, intending to study classical liberalism. Based on political economy, liberalism targets the population and becomes effective through the disciplinary and security dispositifs. On its turn, the law plays the role of internal limit to the practices of government. In the fourth chapter, Law and Order in German Neoliberalism, we proceed to the 1930s, aiming to analyze German neoliberalism or ordoliberalism. Starting from an economic-phenomenological analysis, the ordoliberal governmentality seeks to influence the whole of society, articulating itself as a framework politics. The law ceases to be a limit to the governmental performance and now works as the rules of the economic game. In the fifth chapter, Governmentality and Law in American Neoliberalism, we arrive in the 1960s to approach American neoliberalism or anarcho-capitalism. Founded on an economic analysis of behavior, the American neoliberal art of governing focuses on individuals and functions as an environmental programming strategy. At such a conjuncture, law plays the role of a technology of enforcement. We conclude that, in neoliberal governmentality, legal technology operates as a tactical function of a social and individual programming that aims to promote market freedom. The law is an element of vital importance for the processes of the society’s entrepreneurship and the generalization of the homo oeconomicus model, which characterize neoliberalism at the end of the 20th century.